(untitled) (Economics and region, 2025)
The scientific publication identifies current problems of investment activity in regions. The importance of investments in the regional development of Ukraine and the need for regions to transition to a model of independent survival and functioning have been noted; the use of special mechanisms for financing and attracting investments into the economy of regions has been studied. Investment initiatives for the development of the regional economy during martial law and the prospects for post-war recovery, which have been defined in the State Strategy for Regional Development for 2021-2027 and the Action Plan for the Implementation of the Roadmap for Reforming Public Investment Management for 2024-2028, have been studied. It has been argued that among the important tasks of the strategy, it is worth noting the creation of opportunities for the use of investment resources for the development of the region’s infrastructure, safe business conditions, improving the quality of life of the population, and their comfortable and safe living. The main stages and measures for implementing the public investment management model have been presented. It has been argued that the alternative to the investment activity of regions and territorial communities are mechanisms that provide for the implementation of government and regional programs and projects based on: subventions, preferential lending, financial leasing, factoring, mortgage lending to the population, attracting direct investments, providing funds for the implementation of grant international projects, public-private partnerships, joint ventures, introducing modern investment platforms, etc. The need to attract foreign investments through various forms of collaboration of investment instruments and the importance of international assistance for Ukraine from partner countries during active military operations is proven. The practice of implementing individual mechanisms to support the development of regions and business activity, based on cooperation between the state, international organizations, regions, businesses, and the population, has been considered.